Information Theory in Architecture: Error in Villa Moller, Track House and the Huesca Sports Palace - García Triviño, Francisco (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2018)
Contrary to the origins of information theory, error is part of communication. The so-called “Invisible College” (Palo Alto School) has shown how the elimination of error for the purpose of achieving isomorphic messaging is detrimental to communication. This article applies these theories to architecture, using three different case studies to show how errors have been decisive and inseparable from the final message of each project.